Pemikiran Pendidikan Islam Dalam Aspek Budaya Indonesia - Nurfajiani, Nurfajiani; Akmal Fauzan, Muhammad; Agustian, Raihan; Suryani, Rina (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2025)
This research examines the thoughts on Islamic education within the aspect of Indonesian culture, focusing on the reciprocal relationship between education and culture, as well as the challenges and implementation of Islamic education amidst globalization. The background of this study lies in the importance of understanding how Islamic education can transmit values and culture while adapting to contemporary developments without compromising its fundamental principles. The purpose of this research is to analyze the definitions of education and culture, elaborate on the relationship between Islamic education and culture, identify factors influencing the development of Islamic education in the era of globalization, and present examples of Islamic education implementation within the Indonesian cultural environment. The research method employed in this article is a qualitative descriptive approach, evident from how the article explains concepts and presents relevant examples from literature and interview findings. The results indicate that education and culture mutually advance each other, and Islamic education serves as an essential tool for shaping human civilization by guiding and controlling science and technology in alignment with the fundamental values of faith and piety. Significant challenges in reforming Islamic education during globalization include limitations in competent teaching staff, resources, differing methods, and the need for curriculum renewal. The application of Islamic education in Indonesia is observed through traditional institutions like pesantren, the integration of Islamic values in local traditions and ceremonies, and the use of media and cultural arts as a means of da'wah (Islamic propagation)